Pengaruh Sustainability Reporting Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Panjaitan, Nelly Puspita K.; Asnawi, Meinarni; Sesa, Pascalina Van Sweet (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
The purpose of this study was to analyze and test the effect of sustainability reporting on firm value and profitability as a moderating variable in the influence of sustainability reporting on firm value. Sustainability Reporting is proxied by SRDI (Sustainability Report Disclosure Index), Firm Value is proxied by PBV (Price to Book Value), and Profitability is proxied by ROA (Return on Assets). The population in this study is 246 manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. The sample in this study is 16 manufacturing companies. The sample selection method uses a purposive sampling method. The analysis model used is a simple linear regression model and moderated regression analysis. Data processing is done using the Eviews 12 application. The results of hypothesis 1 in this study show that sustainability reporting does not have a significant effect on company value, then the results of hypothesis 2 show that profitability is able to significantly moderate the relationship between sustainability reporting and company value.